Аlgorithm of diversification management of the enterprise activity - Bielienkova , O.Yu (Ways to Improve Construction Efficiency, 2021)
The algorithm of management of diversification of the enterprise which is based on unity of three main spheres of activity, namely: operational, investment and financial is offered. This combination allows to take into account the comprehensive support of diversification programs and eliminate imbalances and imbalances in the development of enterprises that may arise during the diversification of production. The analysis and generalization of theoretical preconditions of formation of programs of diversification is carried out, the review of sources in the field of management of production programs at the enterprise level, diversification of production, balanced development is carried out. The research methods are comparative analysis and synthesis, reproductive method, modeling. As an indicator of the feasibility of diversification used the excess of future return on capital of the enterprise over its value. A diversification program should be adopted when such a ratio is the maximum of the alternatives for a given development option, and should be rejected if it is not supported in different diversification options. It is revealed that diversification of production activity is one of the ways of development, which affects the investment, financial, operational spheres, leading to sustainable qualitative and quantitative changes of the enterprise. This method of development, acting as a way to reduce risks, helps to increase the financial stability of the enterprise, and hence increase its potential. The created algorithm allows to carry out management of diversification of activity of the enterprise taking into account such important components as cost of the capital and its profitability. The use of the proposed algorithm article is only one of the ways to manage diversification, which should be combined with budgeting, economic and mathematical modeling, methods of expert evaluation, the creation of simulation models and more. Today there is a need to develop indicators of the effectiveness of diversification programs, assess the feasibility of their implementation and develop models that take into account the peculiarities of the functioning of enterprises in different sectors of the economy.